2021
DOI: 10.1002/cbin.11679
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNAs associated with neurodegenerative diseases and diabetic nephropathy in protein l‐isoaspartyl methyltransferase‐deficient mice

Abstract: Protein l‐isoaspartyl methyltransferase (PIMT/PCMT1), an enzyme repairing isoaspartate residues in peptides and proteins that result from the spontaneous decomposition of normal l‐aspartyl and l‐asparaginyl residues during aging, has been revealed to be involved in neurodegenerative diseases (NDDs) and diabetes. However, the molecular mechanisms for a putative association of PIMT dysfunction with these diseases have not been clarified. Our study aimed to identify differentially expressed microRNAs (miRNAs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…Another study performed by Xia et al (23) showed that EVs and their miRNA cargo derived from patients and rats with injured neurons can target osteoprogenitors to promote osteogenesis, suggesting a neuroimmune crosstalk in the bone-brain axis bone homeostasis. Furthermore, consistent with this notion, a recent study reported that EV miR-34a had the same trend of expression in the brain and the kidney of mice deficient in protein L-isoaspartyl methyltransferase, suggesting that EVs may mediate the exchange of signals in the kidney-brain axis (24). Although our study did not investigate the EV cargo, it is important to mention that circulating EVs, particularly their miRNA content, may shed light on this aspect of interorgan crosstalk and indicate that certain EV cargo may play a role in the neuropathological conditions of tissues, encompassing both in the brain and other organs.…”
Section: Discussionsupporting
confidence: 58%
“…Another study performed by Xia et al (23) showed that EVs and their miRNA cargo derived from patients and rats with injured neurons can target osteoprogenitors to promote osteogenesis, suggesting a neuroimmune crosstalk in the bone-brain axis bone homeostasis. Furthermore, consistent with this notion, a recent study reported that EV miR-34a had the same trend of expression in the brain and the kidney of mice deficient in protein L-isoaspartyl methyltransferase, suggesting that EVs may mediate the exchange of signals in the kidney-brain axis (24). Although our study did not investigate the EV cargo, it is important to mention that circulating EVs, particularly their miRNA content, may shed light on this aspect of interorgan crosstalk and indicate that certain EV cargo may play a role in the neuropathological conditions of tissues, encompassing both in the brain and other organs.…”
Section: Discussionsupporting
confidence: 58%
“…The central nervous system (CNS), which consists of the brain and spinal cord, is responsible for the control and regulation of the physiological and psychological activities of every other system in the body. Recent studies have demonstrated that the peripheral and central immune systems, organs, such as the heart, lung, and kidney, and the brain, can all interact with each other in both healthy and pathological conditions, thus, making the communication between the periphery and the brain a topic of growing interest 1–5 . Evidence has demonstrated that brain disorders can cause issues in peripheral organs 6–8 and vice versa; peripheral pathologies can exacerbate a variety of CNS conditions, including Parkinson's Disease (PD), Alzheimer's Disease (AD), hemorrhagic stroke (HS), ischemic stroke (IS), and traumatic brain injury (TBI) 5,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the peripheral and central immune systems, organs, such as the heart, lung, and kidney, and the brain, can all interact with each other in both healthy and pathological conditions, thus, making the communication between the periphery and the brain a topic of growing interest. 1 , 2 , 3 , 4 , 5 Evidence has demonstrated that brain disorders can cause issues in peripheral organs 6 , 7 , 8 and vice versa; peripheral pathologies can exacerbate a variety of CNS conditions, including Parkinson's Disease (PD), Alzheimer's Disease (AD), hemorrhagic stroke (HS), ischemic stroke (IS), and traumatic brain injury (TBI). 5 , 9 , 10 During the process of interaction between the periphery and CNS, the communicators must play critical roles.…”
Section: Introductionmentioning
confidence: 99%